Urgensi penerapan sistem pengendalian internal pada perbankan syariah - Ainiyah, Rizka Nur (Maliki Interdisciplinary Journal, 2025)
In the modern financial era, the internal control system is very important, especially in the context of Islamic banking which has its own characteristics and principles. The implementation of an effective and comprehensive internal control system is a must to ensure compliance with Islamic values, protect customer interests, the approach used is a quantitative approach. The implementation of effective internal control in Islamic banking also includes risk management in accordance with sharia principles. This includes close supervision of the bank's financing, investments and operations to reduce financial and legal risks. Internal controls should be designed and implemented in such a way that they support compliance with sharia principles, while maintaining the integrity and reputation of Islamic financial institutions. Internal control (ICC) has become very important in organizations, especially due to the level of complexity and vast scale of today's businesses. Management often has to rely on various reports and analyses to effectively manage operations, given the breadth of business activities undertaken. In addition, effective internal control can also protect against human weaknesses and reduce the risk of errors or irregularities in operational processes, thereby increasing confidence in the integrity of data and information used in decision making. The urgency of implementing an internal control system in Islamic banking is not only related to compliance, but also to sustainability, efficiency, and trust.